Color Preferences for Morning and Evening Chronotypes - Viera Guzoňová; Kateřina Bočková (Ital Publication, 2022)
The presented paper deals with the symbolism of colors, i.e., color associations. The aim of the paper is to verify the correlation of colors and their symbolism. The combination of color and its meaning was based on the existence of a physiological variable, namely the psychophysiological state. The diurnal preference of individuals was used for this purpose, which divided the subjects according to the chronotype into morning and evening groups. From this starting point, the color preferences of the examined people were monitored in the final phase by means of a color evaluation test. The theoretical part of the paper provides a theoretical framework and starting points for research. The research part describes in detail the research process, especially the methods used. The research itself was attended by 720 people aged 20–40 years. As research methods were used: the Composite scale of morningness, Bourdon's performance test, the Subjective scale of activation, and the Color evaluation test. The respondents had the task of associating colors with their current psychophysiological state. The established hypotheses were mostly confirmed. From a broader point of view, we have come to the conclusion that people attribute certain properties to individual colors, so there is psychic content belonging to individual colors. The colors expressing activity included yellow, orange, and red, and respondents from the group of evening chronotypes also included blue. Calm colors include blue, green, and gray. The most indifferent color was purple. The obtained results were statistically significant. There were also relatively strong correlations in the evaluation of colors due to the psychological focus of the research. Other stimuli for research were also found in the research. Doi: 10.28991/ESJ-2022-06-04-010 Full Text: PDF